A nacre-mimetic superstructure of poly(butylene succinate) structured by using an intense shear flow and ramie fiber as a promising strategy for simultaneous reinforcement and toughening. Issue 43 (25th October 2017) - Xie, Xu-Long; Sun, Qiang-Sheng; Lei, Jun; Tian, Feng; Xu, Ling; Yan, Zheng; Zhong, Gan-Ji; Li, Zhong-Ming
Abstract : Structuring nacre-mimetic superstructures in polymeric materials is an ideal way to enhance simultaneously their strength and toughness. Abstract : Structuring nacre-mimetic superstructures during polymer melt processing could be a promising route to high performance structural materials with exceptional strength and toughness. A nacre-mimetic superstructure characterized with aligned lamellae (stiff phase) glued by amorphous polymer chains (soft and tough phase) was fabricated from a biodegradable polymer of poly(butylene succinate) (PBS) with favorable kinetics of crystallization by using an intense shear flow and promoted by natural ramie fiber. The well-aligned layered structure with a thickness of ∼90 nm for the stiff phase and ∼100 nm for the soft phase was identified with field-emission scanning electron microscopy, and the nacre-mimetic superstructure was quantitatively characterized by space-resolved small angle X-ray scattering. The thicknesses of crystalline lamellae and the amorphous phase layer between crystalline lamellae in the aligned layers were quantitatively assessed to be 3–4 nm and 4–6 nm respectively, indicating that multilayered crystal stacks are formed in the stiff phase. The nacre-mimetic superstructure leads to highly effective load transfer between the stiff phase and soft phase. Thus, the nacre-mimetic superstructure in PBS and the PBS/ramie fiber biocomposite shows simultaneous enhancement in strength and toughness in comparison to common materials without aligned layered structures. Our findings highlight the significance of nacre-mimetic superstructures in polymeric materials and provide novel prospects for the structuring of polymeric materials during melt processing.